2009
DOI: 10.1128/jvi.02579-08
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Porcine Reproductive and Respiratory Syndrome Virus Leader Protease Nsp1α

Abstract: Porcine reproductive and respiratory syndrome (PRRS) virus (PRRSV), a positive-strand RNA virus that belongs to the Arteriviridae family of Nidovirales, has been identified as the causative agent of PRRS. Nsp1␣ is the amino (N)-terminal protein in a polyprotein encoded by the PRRSV genome and is reported to be crucial for subgenomic mRNA synthesis, presumably by serving as a transcription factor. Before functioning in transcription, nsp1␣ proteolytically releases itself from nsp1␤. However, the structural basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 37 publications
5
89
0
2
Order By: Relevance
“…Lines of evidence have shown that nsp1 is processed in vitro into nsp1␣ and nsp1␤ by cis-active PCP1␣ and PCP1␤, respectively, and that this processing occurs cotranslationally and rapidly (8,30,34). The nsp2 protein of PRRSV strain VR-2332, situated immediately downstream of nsp1, is a large multidomain protein of about 1,197 amino acids (aa) containing an N-terminal PL2 cysteine protease, a 500-to 700-aa middle hypervariable region, a putative transmembrane (TM) domain, and a C-terminal tail (13,15).…”
mentioning
confidence: 99%
“…Lines of evidence have shown that nsp1 is processed in vitro into nsp1␣ and nsp1␤ by cis-active PCP1␣ and PCP1␤, respectively, and that this processing occurs cotranslationally and rapidly (8,30,34). The nsp2 protein of PRRSV strain VR-2332, situated immediately downstream of nsp1, is a large multidomain protein of about 1,197 amino acids (aa) containing an N-terminal PL2 cysteine protease, a 500-to 700-aa middle hypervariable region, a putative transmembrane (TM) domain, and a C-terminal tail (13,15).…”
mentioning
confidence: 99%
“…cleaved internally into nsp1␣ and nsp1␤ in the case of PRRSV (and also LDV;denBoon et al, 1995). In type 2 PRRSV, previous studies revealed that the nsp1␣/1␤ cleavage site is located at 180 M/A 181 (P1/P1 ; Chen et al, 2010;Sun et al, 2009). In this study, using the type 1 virus SD01-08, we identified 180 H/S 181 as the corresponding cleavage site in the other PRRSV genotype.…”
Section: Discussionmentioning
confidence: 76%
“…For genotype 2 PRRSV, the nsp1␣/1␤ cleavage site was previously identified to be 180 M/A 181 Sun et al, 2009), but these P1 and P1 residues are not conserved in genotype 1 viruses ( Fig. 2A).…”
Section: Proteolytic Processing Between Prrsv Nsp1˛ and Nsp1ǐmentioning
confidence: 93%
See 1 more Smart Citation
“…RT-PCR was performed to amplify the full-length cDNA using sets of specific primers for hpPRRSV, as described previously [26]. The full-length genome was divided into 18 overlapping cDNA segments.…”
Section: Rna Isolation Rt-pcr and Sequence Analysismentioning
confidence: 99%